Dampak Board of Diversity pada Kinerja Keuangan dan Nilai Pasar Perusahaan: Studi Kasus di Bursa Efek Indonesia - Ningrum, Syntia Cipta (Politeknik Ganesha Medan, 2024)
The study investigates the impact of variety within the board of president on the valuation of companie, utilizing data sourced from entities listed on the Indonesia Stock Exchange. The research goal to assess the influence of board of diversity concerning gender, ethnicity, age, educational background, and professional experience on corporate performance. Employing a methodology of multiple linear regression analysis applied to the financial statements of enterprise, the findings exhibit a notably absolute connection among the board of multeity index and company grade, particularly in terms of financial performance. Notably, factors suchlike as gender, ethnicity, age, scholastic background, and work impression exhibit negligible contributions following the consideration of board of variety. In conclusion, this research underscores the pivotal role of board of variety in increase corporate performance, emphasizing the strategic implication that augmenting diversity within the board can elevate the market value of companies in the Indonesian financial landscape.